(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Sayekti TWDA, Syukur M, Hidayat SH, Maharijaya A, Sobir, Agustina K, Mareza E, Wahyudi A, Supriyanta B. 2024. Performance and yield stability of cayenne peppers (Capsicum frutescens) in multilocation trials in the Indonesian lowlands. Biodiversitas 25: 3008-3017. Cayenne pepper (Capsicum frutescens L.) plant breeding is becoming an increasingly interesting topic due to various usages. The diversity of uses of chilies needs to be balanced with high production and good product quality so that it can meet market needs. This experiment aimed to evaluate the performance and plant diversity of eight elite lines and six commercial varieties of cayenne pepper (C. frutescens) in three different environments. The development of location-specific superior genotypes can be guided to create varieties suited to the targeted environment. This study was conducted in three locations (environments) namely “Lampung”, “Yogyakarta” and “Palembang”. The experiment was conducted using a Randomized Complete Block Design (RCBD) with three replications for each location. Analysis of yield stability was conducted using three methods, namely “Francis-Kanneberg”, “Finlay-Wilkinson” and “AMMI” methods. Among the three locations, the Lampung location experienced a very significant yield loss. This is thought to be due to disease attacks on the plantations. Some genotypes are more suitable for planting at one of the test locations compared to the other two locations. However, there are two genotypes that are stable at three locations based on the three analysis methods used. Genotypes "F1.323340" and "F1.285290” were observed to be stable and produced well at all test locations. Both genotypes can be recommended for planting in lowland environment.